Frontispiece: Diazoacetonitrile (N2CHCN): A Long Forgotten but Valuable Reagent for Organic Synthesis. Issue 1 (2nd January 2020) - Mykhailiuk, Pavel K.; Koenigs, Rene M.
Abstract : An uprising star among the nitrile sources : Diazoacetonitrile (N2 CHCN) is a small reactive diazoalkane, which was synthesized for the first time back in 1898. In contrast to its close analogue ethyl diazoacetate, diazoacetonitrile found only little interest in synthetic chemistry, which might be in part ascribed to the risks associated with its explosion propensity. However, over the course of the last few years, significant progress for the safe access of this diazoalkane has been made and several recent reports showcase its potential. Protocols for the safe generation of diazoacetonitrile, namely in situ generation and flow synthesis, have been developed and opened up a range of chemical applications of this reagent. In their Minireview on page 89 ff., P. K. Mykhailiuk and R. M. Koenigs discuss the synthetic properties and applications of this valuable reagent.